QUALITATIVE RESEARCHING BEYOND TOOLS AND TECHNIQUES - Wilbraham, Lindy (PINS-Psychology in Society, 2025)
Henning, E with Van Rensburg, W & Smit, B (2004) Finding your way in qualitative research. Pretoria: Van Schaik. ISBN 0-627-02545-5 pbk. Pages 179. Finding your way in qualitative research is not simply another qualitative research instruction manual offering tools, techniques and tricks for coding, or quick fixes for methodological mayhem. The text is aimed at social science students and researchers, and while it offers some how-to basics, it mainly claims to attend to “positioning” an investigation within epistemological, theoretical and design logics, and the practice of writing in qualitative inquiry. As its title suggests, finding your way, the text itself is conceived to work inductively to scaffold qualitative inquiry as a process, culminating in “qualitative research design” - as positioned methodological argumentation in writing proposals or reports – in the concluding chapter. As such, Finding your way in qualitative research is situated within an illustrious genre of qualitative research texts attending to paradigmatically situated, in-depth processes of inquiry, design, argument and writing for particular “audiences” (e.g. Van Maanen, 1988; Kvale, 1996; Creswell, 1998; Silverman, 2000). These texts function primarily as overview portals through which other more specialized or applied qualitative methods may be hyperlinked at strategic moments, to fashion a design-concordant, convincing and defendable argument.